THE IMPORTANCE OF TERRITORIAL BEHAVIOR AMONG BLUE TITS (PARUS-CAERULEUS) BREEDING IN A HOLM OAK FOREST - Clamens, A. (Revue D Ecologie-La Terre Et La Vie, 1987)
In a ringed population of Blue Tits (Parus caeruleus) living in a Holm Oak (Quercus ilex) forest of Languedoc, Southern France, and provided with artificial nest-boxes, territorial behaviour plays a major role in limiting the number of breeding pairs. The experimental removal, or the spontaneous disappearance, of a breeding pair is followed by an increase in size of the territories of the neigbouring pairs, or by the arrival of non-ringed juvenile individuals settling in the vacant territory. In a Holm Oak forest without artificial nest-boxes, territorial behaviour does not play such a role, as the major limiting factor in that case is the number of available tree-holes. Pairs of Blue Tits settled on territories where Downy Oaks (Quercus pubescens) are mixed with Holm Oaks, lay their eggs four days earlier on the average, than Blue Tits breeding in pure Holm Oak forest. However, the number of fledglings per brood, and their body weight at 15 days of age, tend to be smaller. The benefit of a later laying date in pure Holm Oak forest quite likely lies in a better synchronization of the maximum nutritional requirements of the young, and of the period of maximum food availability in the environment.
APSAPSThe following values have no corresponding Zotero field: label: Biodiversidade
Keywords: Biodiversidade; breeding pairs; France; holm oak forests; nest-boxes; Parus caeruleus; Quercus ilex